Evaluation of Traceability of Dietary Urine Biochemistry Changes with Commercial Urine Strips - Cebi, Gizem; Caf, Balim Bengisu; Kozan, Esra; Derman, Serap; Celik, Haluk; Tayfun, Miray (MARMARA UNIV, INST HEALTH SCIENCES, 2024)
Objective: This research aims to (i) examine the effects of nutrition on urine biochemistry and (ii) compare the two different measurement methods (laboratory and commercial strip). This means it is desired to bring a new direction to the literature. Methods: The study involved 42 women aged 20-30 from Turkey and examined the urinary excretion of calcium, vitamin C (smoker and non-smoker), sodium, and magnesium based on nutritional status. The collected urine samples were applied onto commercial urine strips, and the resulting color changes were recorded by smartphone; at the same time, it was sent to the laboratory for comparative analysis. The obtained data were used in regression and correlation statistical analysis. All statistical analyzes were performed using IBM SPSS 28.0. Results: While evaluating the regression analysis results in which the excretion due to nutrition was examined, each nutritional level was compared to the restricted intake. ANOVA sig values <.001, t values 1.96 <, in all metabolites (calcium, vitamin C, sodium, magnesium) evaluations. The following rates (R2 2 values) were obtained restricted/optimal nutrition in calcium, vitamin C, sodium, and magnesium: .636, .575, .386, and .209 respectively; restricted/high nutrition in calcium, vitamin C (non-smoker), vitamin C (smoker), sodium, magnesium: .442, .308, .482,.413 and .337 respectively; restricted/supplement in calcium, vitamin C, magnesium: .273, .698 and .799. Calcium and magnesium strips correlated strongly with lab results, correlation coefficients are .679 and .59 respectively. Sodium and creatinine strips correlated very strongly with lab results, correlation coefficients are .876 and .884 respectively. Conclusion: The study revealed that nutrition significantly affected urine excretion levels for calcium, vitamin C, sodium, and magnesium. Additionally, the results showed that urine strips had a correlation with laboratory results indicating their usefulness for pre-diagnosis purposes.
Keywords: Nutrition; urine biochemistry; urinary excretion; commercial urine strip; statistical analyzes.; PREVENTION; Research & Experimental Medicine